2020
DOI: 10.21203/rs.3.rs-133139/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Affect the Survival Status of HIV Infected Patients under ART: The Case of Wolisso Catholic Hospital, Wolisso, Ethiopia, 2016.

Abstract: INTRODUCTION: Monitoring the length of survival after diagnosis is, therefore, an important component of the surveillance of AIDS. It provides a basis for evaluating individual prognostic factors. The survival of patients with AIDS may depend on a variety of factors that are socio-demographic and clinical factors. The study is designed to identify factors that affect the survival status of HIV infected patients under ART in Wolisso, Ethiopia. METHODS: This is a retrospective study based on cases of HIV infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…Patients who were using substances, such as alcohol, tobacco, and chat, or other drugs at baseline, showed almost a 2-fold higher risk of mortality compared to those who did not use substances (AHR = 1.79; 95% CI: 1.40-2.29%). In line, a previous study from Wolisso and Gonder in Ethiopia, revealed that patients who were using substances, like alcohol, tobacco, and chat usage, or other drugs at baseline, presented a 2-fold higher risk of mortality compared to patients who did not use substances [10,11,17,27]. This might be that alcohol, tobacco, and chat, or other drugs utilization can affect patients' immune system, and may speed up the progression of the disease.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Patients who were using substances, such as alcohol, tobacco, and chat, or other drugs at baseline, showed almost a 2-fold higher risk of mortality compared to those who did not use substances (AHR = 1.79; 95% CI: 1.40-2.29%). In line, a previous study from Wolisso and Gonder in Ethiopia, revealed that patients who were using substances, like alcohol, tobacco, and chat usage, or other drugs at baseline, presented a 2-fold higher risk of mortality compared to patients who did not use substances [10,11,17,27]. This might be that alcohol, tobacco, and chat, or other drugs utilization can affect patients' immune system, and may speed up the progression of the disease.…”
Section: Discussionsupporting
confidence: 76%
“…Another study conducted in Tanzania showed TB as a strong predictor of mortality; patients with past TB co-infection had nearly 15-times higher risk of dying as compared to those who did not have TB co-infection. Similar study conducted in Wolisso in central Ethiopia reported past TB co-infection as a predictor of mortality [17]. This might be that delay in diagnosis and treatment as well as no TB prophylaxis contributed to higher mortality.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation